Next-generation sequencing for identifying a novel/de novo pathogenic variant in a Mexican patient with cystic fibrosis: a case report - Angélica Martínez-Hernández; Julieta Larrosa; Francisco Barajas-Olmos; Humberto García-Ortíz; Elvia C. Mendoza-Caamal; Cecilia Contreras-Cubas; Elaheh Mirzaeicheshmeh; José Luis Lezana; Lorena Orozco (BMC, 2019)
Abstract Background Mexico is among the countries showing the highest heterogeneity of CFTR variants. However, no de novo variants have previously been reported in Mexican patients with cystic fibrosis (CF). Case presentation Here, we report the first case of a novel/de novo variant in a Mexican patient with CF. Our patient was an 8-year-old male who had exhibited the clinical onset of CF at one month of age, with steatorrhea, malabsorption, poor weight gain, anemia, and recurrent respiratory tract infections. Complete sequencing of the CFTR gene by next generation sequencing (NGS) revealed two different variants in trans, including the previously reported CF-causing variant c.3266G > A (p.Trp1089*, W1089*), that was inherited from the mother, and the novel/de novo CFTR variant c.1762G > T (p.Glu588*). Conclusion Our results demonstrate the efficiency of targeted NGS for making a rapid and precise diagnosis in patients with clinically suspected CF. This method can enable the provision of accurate genetic counselling, and improve our understanding of the molecular basis of genetic diseases.